Disseminated Amphotericin-Resistant Fusariosis in Acute Leukemia Patients: Report of Two Cases - Pereira, Graziella Hanna; de Angelis, Derlene Attili [UNESP]; Brasil, Roosecelis Araujo; dos Anjos Martins, Marilena; de Matos Castro e Silva, Dulcilena; Szeszs, Maria Walderez; de Souza Carvalho Melhem, Marcia (Springer Nature, 2013)
Disseminated fusariosis has emerged as a significant, usually fatal infection in immunocompromised hosts despite antifungal treatment. We describe here two patients with acute leukemia who developed disseminated amphotericin-resistant fusariosis, and review of six studies of cases series in the literature. Two Fusarium solani strains were isolated from blood and skin cultures of one patient, and one strain from the blood culture of the second patient. Both patients died despite antifungal treatment. Strains were identified by sequencing of ITS1 and ITS4 regions. Random amplified polymorphic DNA analysis of the three F. solani isolates showed a low degree of similarity. Screening for Fusarium spp. contaminants within our facility was negative. Using the CLSI M-38-A2 broth dilution method and E tests®, we found that the MICs were low for voriconazole (0. 12 and 0. 5 mg/L, respectively), unexpectedly high for amphotericin B (≥8 and ≥32 μg/mL, respectively) and itraconazole (≥16 mg/ml). Patients with leukemia or persistent neutropenia should be assessed for disseminated fungal infections, including biopsy and skin cultures. Antifungal susceptibility tests are important due to the possibility of the strains being amphotericin resistant. Treatments must be aggressive, with high doses of antifungals or combined therapy. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Amphotericin resistant; Antifungal; Fusariosis; Fusarium solani; Leukemia; amphotericin B; antifungal agent; fungal DNA; ribosomal spacer DNA; acute biphenotypic leukemia; acute lymphoblastic leukemia; aged; antifungal resistance; case report; chemistry; DNA sequence; drug effect; fatality; fusariosis; Fusarium; genetics; human; isolation and purification; male; microbial sensitivity test; microbiology; pathology; Aged; Amphotericin B; Antifungal Agents; DNA, Fungal; DNA, Ribosomal Spacer; Drug Resistance, Fungal; Fatal Outcome; Humans; Leukemia, Biphenotypic, Acute; Male; Microbial Sensitivity Tests; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Sequence Analysis, DNA